PENDIDIKAN AGAMA ISLAM (Transformasi Potensialitas ke Aktualitas) - Azhar, Sophia (Idaarah: Jurnal Manajemen Pendidikan, 2017)
This paper discusses the transparency of human potentiality through the process of education so actualized in life. As we know that human beings are creatures of Allah that have advantages over other creatures. These advantages because humans have some potential that is not owned by a creature other than humans. These potentials can be actualized in life through the educational process. And the definition of education here is general not only formal and non formal education but lifelong education that applies both in the family, school, and community because the learning process to achieve goodness is valid forever in accordance with Islamic teachings that encourage to seek knowledge ranging from cradle to the grave.